Strengthening parliament as an effective oversight body: the role of ethical political leadership - Zungula, Vuyolwethu (Graduate School of Development Policy and Practice, 2024)
The discussion of Parliament and its role as an oversight body is a significant issue in current South African political and policy discourse. Parliament has in recent years faced scrutiny from the Judiciary (including the Zondo Commission) and the public. This has been due to its perceived weakness as an effective law-making institution as well as its perceived failures in its duty to exercise oversight over the Executive, as enshrined in The Constitution of the Republic of South Africa (Act 108 of 1996). The National Development Plan states that in building a capable developmental state, strong ethical leadership in institutions is required to address South Africa's challenges. Unethical conduct by Members of Parliament (MPs) in recent years has impacted trust in Parliament negatively, as witnessed in Afrobarometer surveys which track citizens' perceptions of public trust levels across institutions. This research examines Parliament's mandate as an instrument of accountability and oversight of the Executive, and in particular what leadership role Members of Parliament, across political parties, can play to strengthen it. Using the qualitative research method, the key factors which inform how consistently MPs from across political parties abide by their Oath of Office, uphold the parliamentary Code of Ethical Conduct, and work to strengthen the effectiveness of Parliament, are critically examined. The study includes recommendations on how both MPs as individuals can be supported to perform their oversight duties and how Parliament as an institution can be strengthened to operate in accordance with its Constitutional mandate. This includes critical consideration and implementation of recommendations the Zondo Commission of Inquiry into State Capture to improve Parliament's oversight function. Additionally, also recommended is a capacity needs analysis, and a mandatory capacity-building programme, that is comprehensive for all MPs and tailored to committees they serve on.